Intranasal Location and Immunohistochemical Characterization of the Equine Olfactory Epithelium - Kupke, Alexandra; Wenisch, Sabine; Failing, Klaus; Herden, Christiane (Frontiers in Neuroanatomy, 2016)
The olfactory epithelium (OE) is the only body site where neurons contact directly the environment and are therefore exposed to a broad variation of substances and insults. It can serve as portal of entry for neurotropic viruses which spread via the olfactory pathway to the central nervous system (CNS). For horses, it has been proposed and concluded mainly from rodent studies that different viruses, e.g. Borna disease virus (BoDV), equine herpesvirus 1 (EHV-1), hendra virus, influenza virus, rabies virus, vesicular stomatitis virus (VSV) can use this route. However, little is yet known about cytoarchitecture, protein expression and the intranasal location of the equine OE. Revealing differences in cytoarchitecture or protein expression pattern in comparison to rodents, canines or humans might help to explain varying susceptibility to certain intranasal virus infections. On the other hand, disclosing similarities especially between rodents and other species, e.g. horses would help to underscore transferability of rodent models. Analysis of the complete noses of 5 adult horses revealed that in the equine OE two epithelial subtypes with distinct marker expression exist, designated as types a and b which resemble those previously described in dogs. Detailed statistical analysis was carried out to confirm the results obtained on the descriptive level. The equine OE was predominantly located in caudodorsal areas of the nasal turbinates with a significant decline in rostroventral direction, especially for type a. Immunohistochemically, olfactory marker protein (OMP) and doublecortin (DCX) expression was found in more cells of OE type a, whereas expression of proliferating cell nuclear antigen (PCNA) and tropomyosin receptor kinase A (TrkA) was present in more cells of type b. Accordingly, type a resembles the mature epithelium, in contrast to the more juvenile type b. Protein expression profile was comparable to canine and rodent OE but equine type a and b were located differently within the nose and revealed differences in its cytoarchitecture when compared to canine OE. Equine OE type a closely resembles rat OE. Whether the observed differences contribute to species-specific susceptibility to intranasal insults such as virus infections has to be further investigated.